2006
DOI: 10.1007/s00253-005-0080-0
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of α-quaternary nonylphenol isomers by Sphingomonas sp. strain TTNP3 involves a type II ipso-substitution mechanism

Abstract: The degradation of radiolabeled 4(3',5'-dimethyl-3'-heptyl)-phenol [nonylphenol (NP)] was tested with resting cells of Sphingomonas sp. strain TTNP3. Concomitantly to the degradation of NP, a metabolite identified as hydroquinone transiently accumulated and short-chain organic acids were then produced at the expense of hydroquinone. Two other radiolabeled isomers of NP, 4(2',6'-dimethyl-2'-heptyl)-phenol and 4(3',6'-dimethyl-3'-heptyl)-phenol, were synthesized. In parallel experiments, the 4(2',6'-dimethyl-2'-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 39 publications
4
63
1
Order By: Relevance
“…Studies of the degradation of NP have shown that this compound is degraded to CO 2 and that HQ is the intermediate used as the sole source of carbon for growth by Sphingomonas sp. strain TTNP3 (6,10). Further degradation compounds that support the hypothesis of a type II mechanism were identified.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Studies of the degradation of NP have shown that this compound is degraded to CO 2 and that HQ is the intermediate used as the sole source of carbon for growth by Sphingomonas sp. strain TTNP3 (6,10). Further degradation compounds that support the hypothesis of a type II mechanism were identified.…”
Section: Discussionmentioning
confidence: 62%
“…Insights into the metabolism of NP by Sphingomonas strains have made clear that the ipso substitution mechanism is not restricted to halogen-substituted phenols (5,6,14). These bacteria are able to break highly stable C-C bonds between an aromatic carbon and the quaternary ␣-carbon of alkylphenol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations